Perinatal health and mother-child health care in the municipality of São Luís, Maranhão State, Brazil - Silva Antônio Augusto M. da; Coimbra Liberata Campos; Silva Raimundo Antônio da; Alves Maria Teresa S. S. de B. e; Lamy Filho Fernando; Lamy Zeni Carvalho; Mochel Elba Gomide; Aragão Vânia Maria de F.; Ribeiro Valdinar Sousa; Tonial Sueli Rosina; Barbieri Marco Antônio (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2001)
The purpose of this article was to evaluate socioeconomic and demographic indicators, reproductive health, use of prenatal, childbirth, and neonatal services, and anthropometric data for mothers and infants. The authors performed a cross-sectional analysis of a systematic sample of 2,831 hospital births in São Luís, Maranhão State, from March 1997 to February 1998 at ten public and private maternity hospitals. The sample was stratified proportionally according to the number of births in each maternity hospital. Mothers answered a standard questionnaire. Of the total, 97.9% were live births and 98% were singletons. Prenatal coverage was 89.5%, and prevalence of cesarean sections was 33.8%. A physician provided prenatal care in 75.7% of cases and performed 73.8% of the deliveries. The Unified Health System covered the costs of 76.4% of the prenatal visits and 89.7% of the deliveries. A pediatrician was present in the delivery room in 50.2% of cases. The low birth weight rate was 9.6% and the preterm birth rate 13.9%. Reasons for concern included a high percentage of adolescent mothers, single mothers (or without partners), the high cesarean rate, and the high percentage of births attended by unqualified personnel.